A NEW SPIN ON 'NON-ROTATING' PORPHYROBLASTS: IMPLICATIONS OF CLEAVAGE REFRACTION AND REFERENCE FRAMES - Kraus J.; Williams P.F. (My University, 2001)
It has been claimed that rigid porphyroblasts which grow before or during folding and concurrent cleavage development do not rotate with respect to the geographical reference frame (GRF), even if the straining is non-coaxial (Bell 1985; Bell and Johnson 1990). The explanation offered is based on strain partitioning. It is argued that the initial orientations of early fabrics included as internal foliations (Si) in the porphyroblasts have been preserved after polyphase deformation, and even after successive orogenies. According to the strain partitioning model, the porphyroblasts are fixed in domains of coaxial straining (microlithons) and are isolated from the non-coaxial straining associated with the enveloping septa (Se). This hypothesis, and also its discussions both pro and contra, suffer from insufficient attention to reference frames. We therefore attempt to demonstrate: (a) the need for rigorous treatment of reference frames in geological interpretations; (b) that, in a folding situation, grains that do not rotate with respect to their immediate matrix generally rotate with respect to the GRF; (c) that lack of porphyroblast rotation with respect to the GRF demands a rare folding mechanism (slip fold model); and (d) that the non-rotation hypothesis is in conflict with heterogeneous deformation (cleavage refraction). Finally, we question the validity of the evidence in a study by Fyson (1980), cited in support of non-rotation with respect to the GRF during folding. Fyson reported orientations of Si that are constant, after folding, over a large area; this scenario is a product of selective data acquisition. In summary, our investigation shows that the lack of porphyroblast rotation with respect to a GRF during folding, while possible, is not universal. The development of microstructures (e.g. curved Si) is only related to the local deformation path, the characterisation of which does not rely on the GRF.